Accidental Extrusion of Sodium Hypochlorite in a Patient Taking Alendronate: A Case Report With an 8-Year Follow-up - Coaguila-Llerena, Hernán [UNESP]; Denegri-Hacking, Antonio; Lucano-Tinoco, Lissy; Mendiola-Aquino, Carlos; Faria, Gisele [UNESP] (Elsevier, 2021)
Extrusion of sodium hypochlorite (NaOCl) is a very rare accident with the most common complications including pain, swelling, and hematoma. It can occur even if procedural guidelines, predisposing conditions, and risk factors are taken into consideration. A 59-year-old female patient was admitted to the endodontics department to treat a left maxillary first premolar (World Dental Federation tooth 24). The medical history included osteoporosis and systemic medication with alendronate. Initially, the diagnosis was “symptomatic irreversible pulpitis” with “normal apical tissues.” During instrumentation of the buccal canal, accidental extrusion of 2.5% NaOCl occurred into the periapical tissues, resulting from misinterpretation of the working length, and caused severe pain and bleeding. The canal was immediately flushed using copious irrigation with saline solution. An analgesic and corticosteroid were prescribed. At 3 and 7 days, ecchymosis and slight hematoma were observed extraorally in the area of the affected tooth and an intraoral ulceration at the apex of the affected tooth. At 15 days, minimal signs of ecchymosis were observed, and the treatment was resumed. At 30 days after the accident, there was complete remission of the sequelae. The clinical, radiographic, and tomographic assessment after 1 month, 1 year, and 8 years showed favorable case evolution. During the 8-year follow-up, the patient maintained the systemic use of alendronate. It can be concluded that NaOCl extrusion is an accident that causes patients and clinicians to experience an unpleasant consequence. The radiographic working length should always be determined carefully. A successful outcome can be achieved in patients who take alendronate.
Keywords: Accident; bisphosphonates; endodontics; root canal therapy; sodium hypochlorite